Analysis of Factors Related to The Implementation of Community Movements for Healthy Living - Florentina Kusyanti; Ima Kristina Yulita (Jurnal Kebidanan, 2022)
Health is the principal capital in improving human resources because physically and mentally healthy people can think and act well. The phenomenon that occurs in Magelang Regency is a change in harmful behavior that affects human health. Many people throw their trash on the side of the access road to the hamlets around Mertoyudan. The sewers look dirty and smelly. Children often litter, spit everywhere, don't wear masks, cough or have flu, and rarely do a health check-up to health workers. All of this illustrates the behavior of people who are not healthy. This community movement program for healthy living is essential to be implemented in Mertoyudan village because the village borders the city; the aim is to accelerate promotive and preventive efforts for healthy living. This type of research is quantitative and qualitative with correlational analysis—the approach used by Cross-Sectional in the Mertoyudan village community. The data used are primary and secondary data, data collection by observation, questionnaires, and in-depth interviews. Frequency distribution data processing, Bivariate with chi-square and multivariate with regression. Characteristics of age at most >45 years old (51.52%), secondary education (51%), status Majority married (81.8%) private occupation (40.9), for univariate knowledge very good (65%) , very good attitude (56.7%), good motivation (55%), good supervision perception (55%), very good effective communication (53.3%) Germas is very good (66.7%) knowledge-germas bivariate ( p=0,000, rho=0,101), attitude-germas (p=0,033, rho=0,275), motivational-germas (p=0,001, rho=0,432), perception of supervision-germas (p=0,002, rho=0,398), Communication -germas (p = 0.052, rho = 0.150), multivariate on the value of F hating obtained a value of 1706.539 with a p-value of 0.000 so that it can be interpreted that all variables have a relationship. The highest univariate result is knowledge, with a result of 65%. For the costab value or the value of the Sparman statistical test, s the value of the highest relationship between motivation and germas is the p-value = 0.001, and the rho value is 0.432, which means that the motivation variable has a moderate relationship strength, but multivariate all variables have a relationship.